The Application of English Learning in Merdeka Curriculum - Fatma, Fatma; Nirwanto, Rahmadi; Qamariah, Zaitun (PT. Padang Tekno Corp, 2024)
This research aims in order to help teachers and students create an effective and current curriculum that includes strategic approaches, teaching methods, and descriptions of challenges and solutions in implementing language learning, the goal of this research is to explain an innovative approach to teaching English to non-native speakers of the language. English taught in Indonesian classrooms A approach for conducting library research was used. Data acquisition through documentation ISI analysis is the method employed. Because Indonesia's educational system was in crisis when this study was being written, it was decided to base its findings on ideas that are frequently utilized in teaching English. The principles of communication, empathy for others, knowledge integration, project-based learning, and technology utilization have been stated above.